Membangun Strategi Keunggulan Bersaing Pada Perusahaan X - Hanif Furqon Abdurrahman; Zulkifli; Miranda W, Agustinus (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2025)
The focus of this thesis is how a company makes strategic planning for a trading business, with the object of research being Company X's business which is classified as a small-medium business in order to develop and maintain competitive advantage in times of disruption or changing conditions through designing the right strategy. This research is a qualitative research with a problem approach through descriptive analysis, regarding Building a Competitive Advantage Strategy in Company X 2023 – 2028. The sampling technique used purposive with Forum Group Discussion followed by qualitative analysis using TOWS, IFE, EFE, CPM and QSPM. The research results obtained are an alternative strategy "Market expansion through various online media" to be the main strategy of company X by improving various systems in the company.